A LIFESTYLE INTERVENTION IN OLDER ADULTS IMPROVES PHYSICAL FATIGABILITY BUT NOT MENTAL FATIGABILITY. (16th November 2018) - Gmelin, T; Santanasto, A; Boudreau, R; Albert, S; Newman, A; Venditti, E; Glynn, N
Abstract: Obesity and physical activity (PA) are associated with physical fatigability in older adults. It is hypothesized that weight loss and PA interventions will improve dimensions of perceived fatigability, physical and mental. Purpose: Examine the impact of a community-based healthy aging and behavioral weight management intervention on change in both physical and mental fatigability among obese community-dwelling older adults enrolled in the 13-month Mobility and Vitality Lifestyle Program (MOVEUP). Methods: We measured perceived physical and mental fatigability using the validated Pittsburgh Fatigability Scale (PFS, range 0–50 for both physical and mental with lower score= less fatigability); self-reported light-moderate PA (LMPA, ≥2.5 METs) using the CHAMPS questionnaire; and weight. Results: At baseline, participants (N=92) were age 68.9 ± 4.1 years, 82.6% female, 25% African American, body mass index 34.2 ± 4.4 kg/m2. Baseline PFS score for physical was 18.9 ± 8.2 and mental 11.3 ± 8.2. After 13 months, participants lost 14.8 ± 13.0 lbs (7.3% of body weight) and increased LMPA by 2.3 hours/week. Concurrently, physical fatigability decreased by 3.2 points (16.9%) to 15.8 ± 8.3 (p=.0005); and mental fatigability had decreased by 0.9 (8%) to 10.4 ± 8.6 (p=.29). Physical, but not mental, fatigability was modestly correlated (-0.22, p=0.04) with change in LMPA after age and sex adjustment; neither were correlated with change in weight loss. Conclusion: Lifestyle interventions may improve physical, but not mental, fatigability. These results provide further evidence that fatigability is multi-dimensional, suggesting that mental and physical fatigability have unique biological pathways. Future work will investigate underlying mechanisms to develop better interventions for reducing fatigability in older adults.